Siting and Sizing of DG for Loss Reduction and Voltage Sag Mitigation in RDS Using ABC Algorithm - Kuruva Siva Ramudu; M. Padma Lalitha; P. Suresh Babu (Institute of Advanced Engineering and Science, 2013)
In order to reduce the power loss and to improve the voltage profile in the distribution system, distributed generators (DGs) are connected to load bus. To reduce the total power loss in the system, the most important process is to identify the proper location for fixing and sizing of DGs. This paper presents a new methodology using a new population based meta heuristic approach namely Artificial Bee Colony algorithm (ABC) for the placement of Distributed Generators (DG) in the radial distribution systems to reduce the real power loss, to improve the voltage profile & voltage sag mitigation. While these power loss reduction, voltage profile improvement and voltage sag mitigation has significant role in lessoning imposed expenditures to utility companies. The power loss reduction is important factor for utility companies because it is directly proportional to the company benefits in a competitive electricity market, while reaching the better power quality standards is too important as it has vital effect on customer orientation. In this paper an ABC algorithm is developed to gain these goals all together. In order to evaluate sag mitigation capability of the proposed algorithm, voltage in voltage sensitive buses is investigated. An existing 20KV network (32-bus system) has been chosen as test network and results are compared with the proposed method in the radial distribution system.DOI:http://dx.doi.org/10.11591/ijece.v3i6.4399